Nanomaterials for green energy - Bhanvase, Bharat A.; Pawade, Vijay B.; Dhoble, Sanjay J., 1967-; Sonawane, Shirish H.; Ashokkumar, Muthupandian (Micro & nano technologies., 2018)
Nanomaterials for Green Energy focuses on the synthesis, characterization and application of novel nanomaterials in the fields of green science and technology. This book contains fundamental information about the properties of novel nanomaterials and their application in green energy. In particular, synthesis and characterization of novel nanomaterials, their application in solar and fuel cells and batteries, and nanomaterials for a low-toxicity environment are discussed. It will provide an important reference resource for researchers in materials science and renewable energy who wish to learn more about how nanomaterials are used to create cheaper, more efficient green energy products.